2004
DOI: 10.1677/joe.0.1820193
|View full text |Cite
|
Sign up to set email alerts
|

The adaptive response of bone to mechanical loading in female transgenic mice is deficient in the absence of oestrogen receptor-alpha and -beta

Abstract: Postmenopausal osteoporosis represents a failure of the response by which bone cells adapt bone mass and architecture to be sufficiently strong to withstand loading without fracture. To address why this failure should be associated with oestrogen withdrawal, we investigated the ulna's adaptive response to mechanical loading in adult female mice lacking oestrogen receptor-(ER / ), those lacking oestrogen receptor-(ER / ) and their wild-type littermates. In wild-type mice, short periods of physiologic cyclic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
80
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 47 publications
9
80
1
1
Order By: Relevance
“…Earlier studies have demonstrated that female but not male mice with ERα inactivation display reduced cortical osteogenic bone response to mechanical loading (19,(21)(22)(23)(24). To determine if the reduced osteogenic response to mechanical loading in female ERα −/− mice is caused by a lack of ERα in osteocytes, we loaded tibiae of female Dmp1-ERα −/− mice and WT mice using a standardized axial loading procedure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies have demonstrated that female but not male mice with ERα inactivation display reduced cortical osteogenic bone response to mechanical loading (19,(21)(22)(23)(24). To determine if the reduced osteogenic response to mechanical loading in female ERα −/− mice is caused by a lack of ERα in osteocytes, we loaded tibiae of female Dmp1-ERα −/− mice and WT mice using a standardized axial loading procedure.…”
Section: Resultsmentioning
confidence: 99%
“…As female mice with total ERα inactivation display reduced cortical osteogenic bone response to mechanical loading (19,(21)(22)(23)(24), and osteocytes are thought to function as the main mechanosensors in bone, it was biologically plausible to hypothesize that ERα in osteocytes is important for the osteogenic response to mechanical loading. However, the cortical osteogenic bone response to mechanical loading was normal in Dmp1-ERα −/− mice, demonstrating that ERα in osteocytes is not crucial for the osteogenic response to mechanical loading and, therefore, further studies are required to identify the ERα target cell type contributing to the osteogenic response to mechanical loading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERα-/-mice produced three times less new cortical bone in response to the same mechanical stimulus as their ERα+/+ littermates [47,48] . Similarly, osteoblasts derived from ERα-/-mice failed to increase in number in response to mechanical stimulation, which can be rescued by transfection with fully functional ERα [49,50] .…”
Section: Effect Of Er Silencing On the Effect Of Genistein Treatmentmentioning
confidence: 90%
“…In the literature, a few studies support ERα's involvement in the adaptive response of osteoblasts to mechanical strain [47][48][49][50] . ERα-/-mice produced three times less new cortical bone in response to the same mechanical stimulus as their ERα+/+ littermates [47,48] .…”
Section: Effect Of Er Silencing On the Effect Of Genistein Treatmentmentioning
confidence: 99%